Agility and Respect. - Holmes, Neville (Computer (00189162), 2009)
The article discusses the challenges and ethical aspects of Agile programming values. The four values that form the basis of agility are expressed as preferences and include working software over comprehensive documentation, customer collaboration over contract negotiation, individuals and interactions over processes and tools, and responding to change over following a plan. The challenge for software engineers is to respect the talent of programmers.